"Anaideia" i opowieść. O "Utopku" Leszka Libery = "Anaideia" and a story. About "Utopek" by Leszek Libera - Mikołajec, Marek (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The primary goal of the considerations in this article is to discuss the novel "Utopek" by Leszek Libera, translated from German by Sława Lisiecka, which tells the story of the writer`s and academician`s hometown (Racibórz in Upper Silesia). Nevertheless, an attempt to explain the aesthetic and ideological meanings of this work is equally important. A significant topic is a modest mention of the scope and originality of the novel?s reception of Libera`s book.
Keywords: anaideia; autotematyzm; powieść łotrzykowska; powieść pikarejska; Śląsk; self-reference; picareaque novel; Silesia